Factors affecting purchasing intention on mobile devices among young consumers / Siti Zulaikha Saiful Bahari - Saiful Bahari, Siti Zulaikha (2015)
Nowadays, mobile phone has become an emerging trend and the fastest growing industries in the globe. The renovation of mobile phone started in 2002, where the first color screen and then introduced the multimedia mobile phone from 2004 to 2006. The innovation of Mobile devices started in 2007 by Nokia (Prlog, 2009).Mobile phone address as ‘Mobile devices’ nowadays because it has more advanced computing power and connectivity than a contemporary mobile devices. In the 20th century, most of devices comes up with ideated and created as a blueprints, prototypes or commercial products. The consumption of mobile devices increased over the recent years.